Compared with Cotrimoxazole Nitroxoline Seems to Be a Better Option for the Treatment and Prophylaxis of Urinary Tract Infections Caused by Multidrug-Resistant Uropathogens: An In Vitro Study - Ulrich Dobrindt; Haleluya T. Wami; Torsten Schmidt-Wieland; Daniela Bertsch; Klaus Oberdorfer; Herbert Hof (MDPI AG, 2021)
The resistance of uropathogens to various antibiotics is increasing, but nitroxoline remains active in vitro against some relevant multidrug resistant uropathogenic bacteria. E. coli strains, which are among the most common uropathogens, are unanimously susceptible. Thus, nitroxoline is an option for the therapy of urinary tract infections caused by multiresistant bacteria. Since nitroxoline is active against bacteria in biofilms, it will also be effective in patients with indwelling catheters or foreign bodies in the urinary tract. Cotrimoxazole, on the other hand, which, in principle, can also act on bacteria in biofilms, is frequently inactive against multiresistant uropathogens. Based on phenotypic resistance data from a large number of urine isolates, structural characterisation of an MDR plasmid of a recent ST131 uropathogenic E. coli isolate, and publicly available genomic data of resistant enterobacteria, we show that nitroxoline could be used instead of cotrimoxazole for intervention against MDR uropathogens. Particularly in uropathogenic E. coli, but also in other enterobacterial uropathogens, the frequent parallel resistance to different antibiotics due to the accumulation of multiple antibiotic resistance determinants on mobile genetic elements argues for greater consideration of nitroxoline in the treatment of uncomplicated urinary tract infections.